Kinetics studies of phytomedicine mathesia - -butyrolactone interaction - H. Nkasa, L.; C. Mulenga, M.; J. Muzomwe, M.; J. Kayembe, S.; B. Ilinga, L.; Z. Kashongwe, M.; P. Ngoy, B.; M Taba, K. (International Journal of Engineering and Technology, 2022)
Kinetic studies of the interaction between Â Î³-Butyrolactone and one of the phytomedecines such as Mathesia used for Buruli ulcer treatment were investigated by conductimetry. Î³-Butyrolactone which is the simplest form of lactone was used as probe in order to fully understand how a cyclic ester, such as lactone, could behave in a basic environment. It was observed that for the Mathesia solution at pH 11 the minimal apparent rate constant was around 3.54636 compare to sodium hydroxyde solution at pH 12 where the minimal apparent rate constant was around 3.12295. The apparent rate constants of successive diluted solutions of Phytomedicine Mathesia show up the dilution factor 1: 4. A plot of apparent rate constant versus dilution factor gave a curve with a correlation coefficient of 0.99831.